Positivity and the Construction of Life Satisfaction Judgments: Global Happiness Is Not the Sum of Its Parts - DIENER, Ed (Institutional Knowledge at Singapore Management University, 2000)
The present study investigated how reports of satisfaction with specific versus global domains can be used to assess a disposition towards positivity in subjective well-being reports. College students from 41 societies (N = 7167) completed measures of life satisfaction and ratings of global and specific aspects of their lives. For example, participants rated satisfaction with their education (global) and satisfaction with their professors, textbooks, and lectures (specific). It was hypothesized that global measures would more strongly reflect individual differences in dispositional positivity, that is, a propensity to evaluate aspects of life in general as good. At both the individual and national levels, positivity predicted life satisfaction beyond objective measures. Also, positivity was associated with norms about ideal life satisfaction such that countries and individuals who highly valued positive emotions were more likely to display positivity. The difference between more global versus more concrete measures of satisfaction can be used as an indirect and subtle measure of positivity.